Impedance Bandwidth Enhancement Using Capacitor-Controlled Series Resonance in an Antenna’s Feeding Structure - Rui Li; Longyue Qu; Hyunwoong Shin; Hoseung Lee; Seokju Wi; Jeonghwan Kim; Hyeongdong Kim (Journal of Electromagnetic Engineering and Science, 2024)
This paper introduces a feeding structure that employs a series capacitor and a parallel capacitor to control input impedance. Accordingly, a wide impedance bandwidth was achieved in a simulation. A comparative analysis of the characteristics of the reference antenna and the proposed antenna was conducted to demonstrate the proposed antenna’s improved bandwidth and enhanced efficiency. According to the simulation and measurement data, the bandwidth of the proposed antenna was approximately 400 MHz (range, 680–1,080 MHz) under a 3:1 voltage standing wave ratio. Moreover, the efficiency improved from 43% to 59% (range, 690–960 MHz), and the radiation pattern showed satisfactory performance. The proposed technology thus offers promising development prospects for the antenna designs of low-frequency systems for mobile communication.